Computer humour: an assessment of public's attitudes towards information technology. - Cho, Janice Kah Yin (2014)
This empirical investigation was undertaken to assess the public's attitudes towards information technology (IT) using an unobtrusive research techniques via IT-related cartoons. The motivation for this study stems from an article written on the research conducted by Anderson [1972]. The article asserted that humour communicates more than happy emotions. Owning to the diverse functions of humour, the research team believes that IT-related cartoons could reveal one’s attitude towards IT more effectively than any other obtrusive methods of assessing attitudes and feelings. Content analysis was carried out on a sample of IT-related cartoons for this study. The analysis by sources concludes that: locals generally possess a more positive attitude than foreigners cartoon found in technical journals reflect more negative attitude towards IT thank those in leisure periodicals and cartoons from books seem to real the individual artist’s personal attitude towards IT. Analysis by themes shows that there is no consistent trend for the occurrence of themes except for three negative themes. Analysis by years reveals that there is generally a gradual acceptance of IT as part of life as advancement of technology continues. A new list of themes was presented in the concluding chapter.